Sensiava longiseta (Copepoda, Calanoida): a new genus and species from the abyss of the Weddell Sea - Markhaseva, Elena L.; Schulz, Knud (Zootaxa, 2006)
Sensiava longiseta gen. et sp. nov. is described from male specimens collected at abyssal depths above the seabed in the Weddell Sea (Southern Ocean). Segmentation and setation of the swimming legs of the new species are typical of the superfamily Clausocalanoidea. Although the new genus shares the presence of sensory setae on the maxilla with the Bradfordian families of the Clausocalanoidea, it does not fit the diagnosis of any of these families. Sensiava longiseta shares with the ancestral group of Bradfordian genera a 1,2,3 setal pattern on the praecoxal endites of the maxilliped and, therefore is provisionally placed within Diaixidae. Sensiava longiseta shows marked asymmetry in the antennule; the right limb is geniculated with ancestral segments XIX–XXIII morphologically modified. The presence of this well pronounced, geniculated antennule is up to now the most striking example of this feature and regarded as an ancestral character in the advanced superfamily Clausocalanoidea.